Baculovirus Induced Transcripts in Hemocytes from the Larvae of Heliothis virescens - Holly J.R. Popham; Jonathan E. Breitenbach; Kent S. Shelby (Viruses, 2011)
Using RNA-seq digital difference expression profiling methods, we have assessed the gene expression profiles of hemocytes harvested from Heliothis virescens that were challenged with Helicoverpa zea single nucleopolyhedrovirus (HzSNPV). A reference transcriptome of hemocyte-expressed transcripts was assembled from 202 million 42-base tags by combining the sequence data of all samples, and the assembled sequences were then subject to BLASTx analysis to determine gene identities. We used the fully sequenced HzSNPV reference genome to align 477,264 Illumina sequence tags from infected hemocytes in order to document expression of HzSNPV genes at early points during infection. A comparison of expression profiles of control insects to those lethally infected with HzSNPV revealed differential expression of key cellular stress response genes and genes involved in lipid metabolism. Transcriptional regulation of specific insect hormones in baculovirus-infected insects was also altered. A number of transcripts bearing homology to retroviral elements that were detected add to a growing body of evidence for extensive invasion of errantiviruses into the insect genome. Using this method, we completed the first and most comprehensive gene expression survey of both baculoviral infection and host immune defense in lepidopteran larvae.